2017
DOI: 10.22159/ajpcr.2017.v10i11.19918
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Isorhamnetin Loaded Poly Lactic-Co-Glycolic Acid Nanoparticles

Abstract: Objective: The aim of the present study was formulation and evaluation of isorhamnetin loaded poly lactic-co-glycolic acid (PLGA) polymeric nanoparticles (NPs). Methods:The present study was designed to incorporate the isorhamnetin in PLGA formulation by double emulsion solvent evaporation method, which offers a dynamic and flexible technology for enhancing drug solubility due to their biphasic characteristic, variety in design, composition and assembly. Synthesized isorhamnetin-PLGA NPs were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…For the development of nanotherapeutics, nanoparticles are characterized using different techniques [ 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ]. Sufficient knowledge of the safety, efficacy, and quality of nanotherapies is required to enable easy translation toward clinical applications [ 211 ].…”
Section: Perspectives For Use Of Ginkgo Biloba In Nanotherapies Of Ne...mentioning
confidence: 99%
“…For the development of nanotherapeutics, nanoparticles are characterized using different techniques [ 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ]. Sufficient knowledge of the safety, efficacy, and quality of nanotherapies is required to enable easy translation toward clinical applications [ 211 ].…”
Section: Perspectives For Use Of Ginkgo Biloba In Nanotherapies Of Ne...mentioning
confidence: 99%
“…However, its targeting capacity is poor due to the poor aqueous solubility and bioavailability, which proves the necessity for the development of the nanoformulations for the most eligible flavonoid molecule in the treatment of cancer. [58] studied the effect of poly lactic-co-glycolic acid isorhamnetin nanoparticles on HepG2 cancer cell lines. They concluded that the nanoformulation of isorhamnetin resulted in a substantial increase in the inhibition of proliferation as compared to the plain isorhamnetin.…”
Section: Isorhamnetinmentioning
confidence: 99%
“…In the prolonged-release dosage form, pasireotide pamoate (10, 20 mg, 30, 40 mg or 60 mg) is evenly distributed among biodegradable microspheres based on poly-D, Llactide-co-glycolide (PLGA). Both copolymers belong to the wellknown family of biocompatible poly (D, L-lactide-co-glycolide) copolymers, which are used for many years in similar commercial drugs [52][53][54]. They consist of lactide and glycolide, which are forming blocks, and degraded to lactic and glycolic acids, physiological to the body and metabolized by normal physiological pathways, and suitable for use in humans for parenteral administration.…”
Section: Pasireotide-ssa With Universal Binding Profilementioning
confidence: 99%